PENGARUH STRATEGI PEMASARAN DAN PELAYANAN PENJUALAN TERHADAP KEPUASAN PELANGGAN PADA PT. WOM FINANCE KECAMATAN PASIR PENYU KABUPATEN INDRAGIRI HULU - Apriansyah, Rocky (Eko dan Bisnis: Riau Economic and Business Review, 2019)
This research is at PT. Wom Finance Pasir Penyu, Indragiri Hulu. The purpose of this study is to determine the effect of marketing strategies and sales services on customer satisfaction at PT. Wom Finance Pasir Penyu, Indragiri Hulu. This research used quantitative methods. By analyzing the data using multiple regression, correlation coefficient, and hypothesis testing using SPSS version 22. The results of the study with the regression equation Y = 5,028 + 0,179X1 + 0,137 X2. a = constant of 5,028 means that customer satisfaction is equal to 5,028 if X1 (marketing strategy) and X2 (sales service) are equal to 0 (zero). b1 = marketing strategy regression coefficient of 0.179 shows that every increase in marketing strategy of one unit and other variables (sales service) is fixed, then there will be an increase in customer satisfaction of 0.179.b2 = regression coefficient of sales services of 0.137 indicates that each increase in sales services is one unit and other variables (marketing strategies) remain, then there will be an increase in customer satisfaction by 0.137. Correlation coefficient is known that R is 0.592 means having a relationship that is being and in the same direction. and then tested with R2 coefficient of determination) is 0.350. this shows that (X1) marketing strategies and (X2) marketing strategies together can contribute to variable (Y) customer satisfaction by 35% and the remaining 65% is contributed by other variables. Hypothesis testing at a significant level = 5% where F count (25,087)> F table (3,09) then Ho is rejected and Ha is accepted. This means that marketing strategy variables and sales services together have a significant effect on customer satisfaction at PT. Wom Finance Pasir Penyu District, Indragiri Hulu Regency. And partial test where t count (3.747)> from t table (1,984) then Ho is rejected and Ha is accepted, which means that the marketing strategy has a significant effect on customer satisfaction and t count (3,081)> than t table (1,984) then Ho is rejected and Ha is accepted, which means that sales services have a significant effect on customer satisfaction